Dampak Game Online Dalam Meningkatkan Prestasi Siswa: TThe Impact of Online Games in Improving Student Achievement - Mofu, Benyamin; Rumthe, Rosina (MURAI: Jurnal Papua Teologi Konstekstual, 2024)
Many people think that online games will have a negative impact on players, this is because online games are associated with violence. Psychologists, pediatricians, and scientists believe that playing online games can have a positive influence. Playing online games can also have a positive impact such as, to improve concentration, develop thinking or reasoning skills, and as entertainment to relieve stress. The type of research used is library research. Literature research is a data collection technique by reviewing books, literature, notes, and various reports related to the problem to be solved (Nazir.1988). The impact of Online Games includes relieving stress, filling spare time, adding friends, and earning income. In addition, the purpose of playing online games is because you want to participate in competitions. Online games can have a positive impact on players, that is, online games are useful for improving students' thinking skills, training students to be proficient in English, increasing intelligence and sharpening the brain, and also online games can help students to improve soft skills.